PARADOKS EFEKTIVITAS MBS: KONTRADIKSI ANTARA KEUNGGULAN TATA KELOLA INTERNAL DAN KETERBATASAN DUKUNGAN FINANSIAL SEKTORAL - Chindytia; Anak Agung Gede Agung; Ni Komang Dyah Tri Rahma Wraspati; Ni Kadek Dina Yuliartini; Anak Agung Istri Mirah Pradnya Paramitha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to analyze the paradoxical phenomenon between the quality of internal school governance and the reality of infrastructure limitations at SD No 3 Sading. A descriptive qualitative approach using the case study method was employed, with data collected through observation, interviews, and School-Based Management (SBM) assessment instruments. The results show that, quantitatively, SBM implementation is in the "Good" category with a score of 81/100, supported by very strong administrative compliance. However, qualitatively, a significant disconnection was found in the form of physical infrastructure damage and high teacher workloads due to dual administrative roles. The study concludes that the sustainability of school quality relies heavily on leadership resilience and community social capital, which function as a substitute mechanism for the lack of sectoral financial support from the government. Synchronization between managerial achievement and physical assistance priorities is an urgent necessity for future educational policies.